Stretching and Contraction of Extensional Basins With Pre-Rift Salt: A Numerical Modeling Approach - Granado, Pablo; Ruh, Jonas B.; Santolaria, Pablo; Strauss, Philipp; Muñoz, Josep Anton (Frontiers in Earth Science, 2021)
We present a series of 2D thermo-mechanical numerical experiments of thick-skinned crustal extension including a pre-rift salt horizon and subsequent thin-, thick-skinned, or mixed styles of convergence accompanied by surface processes. Extension localization along steep basement faults produces half-graben structures and leads to variations in the original distribution of pre-rift salt. Thick-skinned extension rate and salt rheology control hanging wall accommodation space as well as the locus and timing of minibasin grounding. Upon shortening, extension-related basement steps hinder forward propagation of evolving shallow thrust systems; conversely, if full basin inversion takes place along every individual fault, the regional salt layer is placed back to its pre-extensional configuration, constituting a regionally continuous décollement. Continued shortening and basement involvement deform the shallow fold-thrust structures and locally breaches the shallow décollement. We aim at obtaining a series of structural, stratigraphic and kinematic templates of fold-and-thrust belts involving rift basins with an intervening pre-rift salt horizon. Numerical results are compared to natural cases of salt-related inversion tectonics to better understand their structural evolution.